Evaluation of planning aims and dose prescription in image-guided adaptive brachytherapy and radiochemotherapy for cervical cancer: Vienna clinical experience in 225 patients from 1998 to 2008. (21st October 2015) - Majercakova, Katarina; Pötter, Richard; Kirisits, Christian; Banerjee, Susovan; Sturdza, Alina E.; Georg, Petra; Nesvacil, Nicole; Schmid, Maximilian P.
ABSTRACT: Background. To assess planning aims (PAs) and dose prescription in image-guided adaptive brachytherapy (IGABT) of cervical cancer and investigate potential impact on clinical outcome. Material and methods. Our study population consists of 225 consecutive cervical cancer patients (FIGO stages IB–IVA) treated between 1998 and 2008 at the Medical University of Vienna by external beam radiotherapy (EBRT) ± chemotherapy and IGABT. For this retrospective study, patients were stratified into two treatment groups: PA+ group, all dose constraints fulfilled for prescription; PA-, one or more dose constraints not fulfilled for prescription. The following dose constraints (EBRT+ IGABT) were applied: clinical target volume (CTV)HR D90 ≥ 85 Gy, D2cm3 Rectum < 70 Gy, D2cm3 Bladder < 90 Gy. Differences in patient, tumor and treatment characteristics and clinical outcome (event: local failure or grade 3 + 4 toxicity) were compared between Group 1 and 2. Further, the impact of learning period (1998–2000) and protocol period (2001–2008) on the fulfillment of PAs for dose prescription and clinical outcome was analyzed. Results . In the PA+ group there were 77 (34%) and in the PA- group 148 (66%) patients. In the PA- group, CTVHR D90 < 85 Gy was prescribed in 82 patients, D2cm3 bladder > 90 Gy was prescribed in 80 patients and D2cm3 Rectum > 70 Gy in 60 patients. Fulfillment of the PA for dose prescription improved from 4% in the learning period to 48% in the protocol period. The five-year event-free interval was 64% in the learning period and 84% in the protocol period (p = 0.008). Conclusion. Fulfillment of all PAs for dose prescription is challenging – especially in patients with more advanced tumors. However, with growing experience fulfillment of PA for dose prescription can be significantly increased (learning and protocol period). Such increase in fulfilling PA for dose prescription is followed by a significant improvement in clinical outcome.